2020
DOI: 10.3390/catal10020243
|View full text |Cite
|
Sign up to set email alerts
|

Co-Supported CeO2Nanoparticles for CO Catalytic Oxidation: Effects of Different Synthesis Methods on Catalytic Performance

Abstract: Hydrothermal and co-precipitation methods were studied as two different methods for the synthesis of CeO 2 nanocatalysts. Co/CeO 2 catalysts supported by 2, 4, 6, or 8wt% Co were further synthesized through impregnation and the performance of the catalytic oxidation of CO has been investigated. The highest specific surface area and the best catalytic performance was obtained by the catalyst 4wt% Co/CeO 2 with the CeO 2 support synthesized by the hydrothermal method (4% Co/CeO 2 -h), which yielded 100% CO conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…As can be seen, MgO-36 showed the highest surface area (34.6 m 2 /g) with the smallest crystallite size (29.9 nm) among other MgO catalysts, while MgO-48 showed the smallest surface area (13.5 m 2 /g) with the biggest crystallite size (48.4 nm). The result obtained was also in agreement with the study carried out by Sui et al [34] that showed CeO 2 support, and the Co/CeO 2 catalyst exhibited a smaller particle size correlated with a higher specific surface area. For 30Ce/MgO catalysts, 30Ce/MgO-48 also showed the highest surface area (29.3 m 2 /g) compared to other 30Ce/MgO catalysts.…”
Section: Catalyst Characterizationsupporting
confidence: 92%
“…As can be seen, MgO-36 showed the highest surface area (34.6 m 2 /g) with the smallest crystallite size (29.9 nm) among other MgO catalysts, while MgO-48 showed the smallest surface area (13.5 m 2 /g) with the biggest crystallite size (48.4 nm). The result obtained was also in agreement with the study carried out by Sui et al [34] that showed CeO 2 support, and the Co/CeO 2 catalyst exhibited a smaller particle size correlated with a higher specific surface area. For 30Ce/MgO catalysts, 30Ce/MgO-48 also showed the highest surface area (29.3 m 2 /g) compared to other 30Ce/MgO catalysts.…”
Section: Catalyst Characterizationsupporting
confidence: 92%
“…56 For the bulk CeO 2 sample, the two main reduction peaks are concentrated at 536 and 857 °C, respectively. 57 The first peak is attributed to consumption of hydrogen by non-stoichiometric superficial Ce 4+ , and the other peak is related to the reduction of Ce 4+ to Ce 3+ in the bulk phase. 58,59 Compared with the bulk CeO 2 and Mn 2 O 3 , the CeO 2 –MnO x composite oxide samples exhibit two reduction peaks at ∼280 and 380 °C, which are attributed to the reduction of MnO x species in the CeO 2 –MnO x composite oxides.…”
Section: Resultsmentioning
confidence: 99%
“…In case of heterogeneous catalyst, the extent of adsorption of reactants on the surface of catalyst decides the activity of catalyst [71] . The amount of catalyst into the reaction medium defines the active sites and hence controls the productivity and selectivity of the desired product [72] . However, the influence of CuO/CeO 2 /ZnO catalyst loading on glycerol conversion, GC yield and selectivity was studied.…”
Section: Resultsmentioning
confidence: 99%
“…[71] The amount of catalyst into the reaction medium defines the active sites and hence controls the productivity and selectivity of the desired product. [72] However, the influence of CuO/CeO 2 /ZnO catalyst loading on glycerol conversion, GC yield and selectivity was studied. The influence of CuO/CeO 2 /ZnO catalyst concentration on Glycerol conversion, GC yield and selectivity is shown (Figure 7).…”
Section: Influence Of 5 Wt % Cuo/ceo 2 /Zno Catalyst Concentrationmentioning
confidence: 99%